AB0123 CCL17 IN SYNOVIAL FLUID AND PLASMA OF PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS. (June 2019) - Hor, Cecil; Achuthan, Adrian; Lim, Keith; Hamilton, John
Abstract : Background: Despite the advancements in management of rheumatoid arthritis (RA) in the last two decades, there are still a significant number of patients who cannot achieve low disease states or remission with the current available therapy. Granulocyte macrophage-colony stimulating factor (GM-CSF) is a key mediator in inflammation and autoimmunity, and has emerged as a novel therapeutic target in RA. However, potential adverse side effects warrant further investigation of a more specific target. Objectives: Chemokine (C-C motif) ligand 17 (CCL17) is a downstream mediator of GM-CSF and has recently been shown to be regulated by GM-CSF in human monocytes. Significantly, CCL17 has a non-redundant role in inflammatory arthritis and pain. We investigated the expression levels of CCL17 in synovial fluid and plasma from RA patients. Methods: We recruited RA patients with symptomatic swollen joints, who require joint aspiration for diagnostic and/or therapeutic purposes. Synovial fluid and plasma were collected and CCL17 protein levels were determined by ELISA. Results: CCL17 protein was measured in synovial fluid and plasma samples from our cohort of RA patients. Levels of secreted CCL17 were higher in plasma [median 240 (40-580) pg/ml] compared to synovial fluid [median 100 (30-300) pg/ml] p<0.05. Conclusion: Significant levels of CCL17 were detected in RA synovial fluid and plasma. This is a novel study which demonstrates and compares the presence of CCL17 in synovial fluid and plasma from matching RA patients. The expression of CCL17 in plasma can make it a useful potential biomarker for RA, while its expression in synovial fluid suggests that CCL17 may be a therapeutic target for treating RA. References: [1] Gibofsky, A., Epidemiology, pathophysiology, and diagnosis of rheumatoid arthritis: A Synopsis. Am J Manag Care, 2014. 20(7Suppl): p. S128-35. [2] Hamilton, J.A., GM-CSF as a target in inflammatory/autoimmune disease: current evidence and future therapeutic potential. Expert Rev Clin Immunol, 2015. 11(4): p. 457-65. [3] Achuthan, A., et al., Granulocyte macrophage colony-stimulating factor induces CCL17 production via IRF4 to mediate inflammation. J Clin Invest, 2016. 126(9): p. 3453-66. Disclosure of Interests: Cecil Hor Speakers bureau: Mundipharma, Pfizer, Adrian Achuthan: None declared, Keith Lim Consultant for: Advisor for role of hepatitis and TB in Cimzia, UCB, Speakers bureau: Role of biological in pregnancy UCB, John Hamilton Grant/research support from: GSK